Comparative in vitro dermal absorption of moxidectin and doramectin through bovine skin - Sallovitz, Juan Manuel (2008)
Endectocide drugs are used topically to treating ruminant parasitic diseases due to their easy administration, which also avoids residues in an edible administration site. However, available knowledge on their transdermal absorption in cattle is scarce. A practical in vitro method to evaluating new topical formulations before in vivo assays is not available. The transdermal absorption of moxidectin and doramectin topical formulations was evaluated using an in vitro model of bovine epidermis. Epidermal layers (500 µm) were placed on modified Franz diffusion cells. Receptor medium was buffer phosphate (0.1 M), albumin and ethanol (76:4:20). Sampling ranged from 0 to 48 h post-administration. Drug concentrations were quantified by HPLC. By 16.2±6.9 h (MXD) and 33.2± 6.3 h (DRM) postadministration, permeation plateaus were reached. Permeation flows (MXD: 3.8±3.1, DRM: 10.1 ± 8.1 ng·cm-2 ·h-1 ) differed statistically (P<0.05). Permeation coefficients (MXD: 1.6x10- 06± 1.3x10-06 cm/h, DRM: 4.12x10-06 ± 3.44x10-06 cm/h) were similar (P>0.05). These results agree with the faster plateau and shorter Tlag of MXD (2.4± 0.6 h) compared to DRM (12.2 ± 5.4 h), which could be due to different lipophilicity. Results are in agreement with in vivo kinetic data. The in vitro model presented here is useful to predicting and further understanding of endectocides‟ transdermal absorption process in cattle.